2022
DOI: 10.1039/d2ra04266e
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabutylammonium bromide-based hydrophobic deep eutectic solvent for the extraction and separation of dihydromyricetin from vine tea and its inhibitory efficiency against xanthine oxidase

Abstract: In this study, deep eutectic solvent oscillation-assisted extraction (DES-OS) combined with macroporous resin adsorption and desorption technology was used to achieve the rapid green extraction and separation of dihydromyricetin (DMY) from vine tea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The benzene ring can generate an accumulated hydrophobic effect with the hydrophobic residues, and the hydroxyl oxygen can form a hydrogen bond with the side chains of numerous residues. As a result, hydrophobicity, hydrogen bonding, and electrostatic contact all work together to keep ligand molecules together (Wang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The benzene ring can generate an accumulated hydrophobic effect with the hydrophobic residues, and the hydroxyl oxygen can form a hydrogen bond with the side chains of numerous residues. As a result, hydrophobicity, hydrogen bonding, and electrostatic contact all work together to keep ligand molecules together (Wang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The total yield of five components was 3.92 ± 0.03 mg g −1 , which was higher than traditional organic solvents. Wang et al 17 adopted a low eutectic solvent oscillation-assisted extraction (DES-OS) combined with a macroporous resin adsorption–desorption technique to achieve rapid green extraction and separation of dihydromyricetin (DMY), a characteristic component of vine tea. Multivariate data analysis demonstrated that the DES system composed of tetrabutylammonium bromide (N 444 Br) and pyruvate (molar ratio: 1 : 2) enhanced the destruction of the DMY cell wall structure, resulting in the release of more DMY and good extraction performance.…”
Section: Introductionmentioning
confidence: 99%
“…It allows obtaining extracts with higher active substances content, 43 isolate them from industrial plant waste, 44 improve the quality of essential oils, 45 and enhance in vivo bioavailability. 46 Tetrabutylammonium salts are promising for the same purposes, [47][48][49][50] but they are still weakly presented in this field.…”
mentioning
confidence: 99%